2013
DOI: 10.1007/s10616-013-9636-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sea anemone (H. magnifica) venom on two human breast cancer lines: death by apoptosis

Abstract: Venom from the sea anemone, Heteractis magnifica, has multiple biological effects including, cytotoxic, cytolytic and hemolytic activities. In this study, cytotoxicity induced by H. magnifica venom was investigated using the crystal violet assay on human breast cancer T47D and MCF7 cell lines and normal human breast 184B5 cell line. Apoptosis was also assayed via Annexin V-flourescein isothiocyanate and propidium iodide (PI) staining followed by flow cytometric analysis. Cell cycle progression and mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
1
14
0
3
Order By: Relevance
“…Our previous work demonstrated that H. Magnifica venom induced apoptosis by loss ofmitochondrial membrane potentialof human non-small cell lung cancer A549 cells [13] . These findings are consistent with our previous study on T47D and MCF7 cell lines that the venom significantly increased the percentage of cells positive for JC-1 monomers [12] .…”
Section: Introductionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our previous work demonstrated that H. Magnifica venom induced apoptosis by loss ofmitochondrial membrane potentialof human non-small cell lung cancer A549 cells [13] . These findings are consistent with our previous study on T47D and MCF7 cell lines that the venom significantly increased the percentage of cells positive for JC-1 monomers [12] .…”
Section: Introductionsupporting
confidence: 93%
“…In contrast, H. magnifica venom applied to human breast cancer T47D and MCF7 cells was found to induce cell cycle arrest in sub G1 phase with a concomitant decrease in the G1 phase, indicating induction of apoptosis [12] . This discrepancy might be due to the difference in cell type analysed.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations